AUDIT COMMITTEE, CAPITAL STRUCTURE AND LIQUIDITY: INTERACTION AND IMPACT ON EARNINGS QUALITY - Agoestina Mappadang (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The purpose of this research is to determine the effect of capital structure and liquidity on earnings quality with the audit committee as a moderating variable. The research population was manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period 2017-2019 totaling of 144 companies. The sampling method used was purposive sampling and obtained 40 companies as a sample. The data analysis used was mulpiple regression and run under SPSS rogram. The result shows that capital structure, liquidity, and committee audit silmutaneusly affect earnings quality. Partially, capital structure has negative significance effect on earnings quality, and liquidity has no significant effect on earnings quality. Meanwhile committee audit able to strengthen the effect of capital structure on earnings quality, and committee audit do not able to strengthen the effect of liquidity on earnings quality.